Critical Analysis of Islamic Digital Marketing as Business Strategy: Study at the Cianjur Grilled Fish Restaurant - Retnowati, May Shinta; Sukoco, Daud; Firda Rahmi Aliya Putri, Sri (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2024)
The development of information and communication technology was increasingly. Which can be used as one of the media in efforts to develop business ventures. One form of technological innovation is in the form of promoting products produced through digital marketing strategies by utilizing social media by using Islamic Marketing. The purpose of this study is to find out and analyze the use of digital marketing through social media as marketing strategy at the Cianjur grilled fish restaurant as an effort to develop business at the restaurant. This type of research is using qualitative descriptive analysis approach. The research data is in the form of primary data obtained through interviews with one of the managers at the Cianjur grilled fish restaurant who has used digital marketing to market their products and has succeeded in increasing sales turnover, while secondary data is obtained from journals, books and literature studies related to digital marketing for business people. The conclusion that can be drawn from the results of this study is that the use of digital marketing strategies through social media is very influential on business development in Cianjur grilled fish restaurants, because the application of digital marketing causes businesses to be recognized more quickly by the public so that this becomes one of the factors for business development as a whole fast